2003
DOI: 10.1007/bf03040888
|View full text |Cite
|
Sign up to set email alerts
|

Umgang mit Schmerz und Stress an der Neonatologischen Intensivstation. Eine Evaluation in Österreich

Abstract: There is widespread awareness among neonatologists of the importance and effects of distress caused by pain in newborns. However, the necessity of providing sufficient analgesia is underestimated. Further information on the safety of analgesic drugs in neonatology is imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Therefore, it is concerning that only half of the respondents to this survey believed pain assessment tools to be reliable and valid, and only half routinely use them. Similarly concerning are the results of previous studies of NICUs in Australia, Italy and Austria which reported pain assessment tool use rates at 6%, 19% and 11%, respectively 9,18,19 . Doctors with more neonatal experience were more likely to believe pain assessment tools to be reliable and valid, suggesting that earlier education of junior doctors may be valuable.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, it is concerning that only half of the respondents to this survey believed pain assessment tools to be reliable and valid, and only half routinely use them. Similarly concerning are the results of previous studies of NICUs in Australia, Italy and Austria which reported pain assessment tool use rates at 6%, 19% and 11%, respectively 9,18,19 . Doctors with more neonatal experience were more likely to believe pain assessment tools to be reliable and valid, suggesting that earlier education of junior doctors may be valuable.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly concerning are the results of previous studies of NICUs in Australia, Italy and Austria which reported pain assessment tool use rates at 6%, 19% and 11%, respectively. 9,18,19 Doctors with more neonatal experience were more likely to believe pain assessment tools to be reliable and valid, suggesting that earlier education of junior doctors may be valuable. This is supported by the results of a United Kingdom study in which lack of education was the most common reason given by nurses for not utilising pain assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative studies examined specific aspects of DSC, including pain relief, 31,32 visiting practices, 33 control of lighting and noise, 34 staff training in NIDCAP, 35 use of the NIDCAP and developmental teams, 21 and nursing-care procedures. 22 Comprehensive quantitative comparisons of the multiple facets of DSC in NICUs, within and between countries, are still few and far between.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the systematic review were that small volumes of sucrose or other sweet tasting solutions, compared with either placebo solutions or no treatment, were effective in reducing behavioural signs of pain and multi-dimensional behavioural and composite pain scores during and following completion of either heel lance or venepuncture. Despite this large body of evidence demonstrating the analgesic properties of oral sucrose in infants, and despite recommendations that sucrose be used during painful procedures, by national and international professional bodies concerning pain management in infants (American Academy of Pediatrics, Canadian Paediatric Society, 2000;Anand, 2001;Royal Australasian College of Physicians, 2005) infrequent utilisation of oral sucrose in the clinical setting has been reported (Fernando et al, 2001;Gray et al, 2006;Rohrmeister et al, 2003).…”
Section: Introductionmentioning
confidence: 95%